Interaction of Serum Alkaline Phosphatase and Folic Acid Treatment on Chronic Kidney Disease Progression in Treated Hypertensive Adults - Zhang, Yuanyuan; He, Panpan; Wang, Guobao; Liang, Min; Xie, Di; Nie, Jing; Liu, Chengzhang; Song, Yun; Liu, Lishun; Wang, Binyan; Li, Jianping; Zhang, Yan; et al. (Frontiers in Pharmacology, 2022)
The relation of alkaline phosphatase (ALP) with chronic kidney disease (CKD) is still uncertain. We aimed to examine the prospective association between serum ALP and CKD progression, and the modifying effect of serum ALP on folic acid in preventing CKD progression in treated hypertensive patients. This is a post-hoc analysis of 12,734 hypertensive adults with relevant measurements and without liver disease at baseline from the renal sub-study of the China Stroke Primary Prevention Trial, where participants were randomly assigned to daily treatments of 10mg enalapril and 0.8mg folic acid, or 10mg enalapril alone. The primary outcome was CKD progression, defined as a decrease in estimated glomerular filtration rate (eGFR) of ≥30% and to a level of <60mL/min/1.73m2 if baseline eGFR was ≥60 mL/min/1.73m2; or a decrease in eGFR of ≥50% if baseline eGFR was <60mL/min/1.73m2; or end-stage renal disease. Over a median of 4.4 years, in the enalapril only group, participants with baseline serum ALP≥110IU/L (quartile 4) had a significantly higher risk of CKD progression (3.4% vs. 2.3%; adjusted OR,1.61; 95%CI:1.11, 2.32), compared with those with ALP<110IU/L. For those with enalapril and folic acid treatment, compared with the enalapril only treatment, the risk of CKD progression was reduced from 3.4% to 2.1% (adjusted OR,0.53; 95%CI:0.34, 0.83) among participants with baseline ALP≥110IU/L, whereas there was no significant effect among those with ALP<110IU/L. In hypertensive patients, higher serum ALP was associated with increased risk of CKD progression, and this risk was reduced by 47% with folic acid treatment.